Adaptive Governance and Collaborative Innovation in Global Sustainability Contexts - Safri (Novatio : Journal of Management Technology and Innovation, 2025)
This study examines the role of knowledge management (KM) in enabling open innovation (OI) networks. The review synthesizes existing literature and analyzes the systemic barriers that constrain effective KM practices. A systematic narrative review methodology was adopted, drawing on peer-reviewed studies from databases including Scopus, Web of Science, Google Scholar, and PubMed. Keywords such as “knowledge management,” “open innovation,” “digital platforms,” and “communities of practice” guided the literature search. The findings reveal three dominant themes: the integration of digital technologies to facilitate knowledge sharing, the establishment of collaborative environments through Communities of Practice, and the importance of organizational adaptability in dynamic contexts. Organizational, technological, and cultural factors strongly influence KM effectiveness, with significant variation across regional contexts. Developed economies benefit from robust infrastructures, while developing regions face resource constraints that limit participation in innovation networks. Comparative insights highlight best practices such as corporate accelerators, digital collaboration platforms, and multicultural leadership training. This review concludes that advancing KM in open innovation requires investments in digital infrastructure, inclusive leadership, and collaborative frameworks